2019
DOI: 10.1556/2060.106.2019.33
|View full text |Cite
|
Sign up to set email alerts
|

Proprioceptive accuracy is not associated with self-reported body awareness, body competence, and affect

Abstract: Purpose: Proprioception plays an essential role in motor control and in psychological functioning: it is the basis of body schema and the feeling of body ownership. There are individual differences in the processing accuracy of proprioceptive stimuli. Although proprioceptive acuity plays an important role in physical competence, there are contradictory findings concerning the role it plays in healthy psychological functioning. This study aims to shed more light on this association. Material and methods: Sixty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Finally (H4), we replicated the findings on the independence of proprioceptive accuracy and interoceptive sensibility and body competence ( Horváth et al, 2019 ) and extended them to another proprioceptive modality (weight discrimination) and confidence rating. The lack of association between interoceptive sensibility, a construct that integrates interoceptive experience across multiple channels, and interoceptive confidence ratings is particularly intriguing.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Finally (H4), we replicated the findings on the independence of proprioceptive accuracy and interoceptive sensibility and body competence ( Horváth et al, 2019 ) and extended them to another proprioceptive modality (weight discrimination) and confidence rating. The lack of association between interoceptive sensibility, a construct that integrates interoceptive experience across multiple channels, and interoceptive confidence ratings is particularly intriguing.…”
Section: Discussionsupporting
confidence: 70%
“…However, not all studies confirmed the aforementioned relationships, there are null findings too, for example with respect to schizophrenia ( Ritzler and Rosenbaum, 1974 ; Ritzler, 1977 ), fibromyalgia ( Akyol et al, 2013 ; Ulus et al, 2013 ), and chronic pain ( Tsay et al, 2015 ). Moreover, Horváth et al (2019) found that there is no association between trait affect and proprioceptive accuracy, as assessed with the Joint Position Reproduction test in the elbow joint. Additionally, proprioceptive accuracy was not correlated with body awareness–a construct that overlaps with interoceptive sensibility ( Ferentzi et al, 2020 )–and perceived body competence ( Ferentzi et al, 2017 ; Horváth et al, 2019 ).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation